“I don’t feel like I fit the math mold:” Identity Resources of Queer-Spectrum Students in Mathematics - Voigt, Matthew (Perspectivas da Educação Matemática, 2024)
This paper presents findings from the qualitative portion of a larger mixed-methods study using thematic analysis with data from student focus groups focused on the experiences of queer-spectrum students in Mathematics. Drawing on Nasir’s identity resource constructs, this study sheds light on the material, relational, and ideational resources impacting queer-spectrum students majoring in STEM. Three key findings emerged from the data: (1) smaller "safe spaces" and relationships within STEM environments fostered robust participation among queer-spectrum students (2) resources supporting academic and social integration, such as Out in STEM and positive instructor relationships, were crucial for fostering a sense of belonging, and (3) the lack of positive ideational resources, including the absence of queer role models and historical discrimination in STEM, contributed to a sense of exclusion among queer-spectrum students. Efforts to diversify STEM must address these challenges by promoting supportive environments that value diverse identities. Future research should examine how identity resources are made available in diverse institutional contexts to better support queer-spectrum students in developing robust math identities.